Profil Belanja Wisatawan Pantai Gedambaan Kabupaten Kotabaru - Selviani, Rima; Maulina, Dessy (PPJP ULM, 2024)
This study aims to determine the characteristics of tourists and the tendency of spending on Gendambaan Kotabaru beach tourists. This research is quantitative by using primary data obtained through direct interviews with tourists visiting Gedambaan Kotabaru Beach. This study used purposive sampling techniques. The results showed that the characteristics of tourists visiting Gedambaan Beach mostly come from outside Kotabaru. The average expenditure of tourists from outside the region is much more than tourists from the Kotabaru area. Kotabaru's local tourist expenditure amounted to 155,023 with a proportion of 17225. Meanwhile, tourist expenditure outside Kotabaru amounted to 287,950 with a proportion of 14398.